Pelatihan Manajemen Keuangan Pemerintah Daerah untuk Meningkatkan Efisiensi dan Transparansi di Kabupaten Toraja Utara - Seseang, Rahmawati Haji; Syamsuddin, Syamsuddin; Indrijawati, Aini (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
This community service activity aimed to strengthen the financial management capacity of local government apparatus in North Toraja Regency through structured training. The background was rooted in findings from the Audit Board of Indonesia (BPK), which revealed weaknesses in the internal control system, asset management, and budgetary sustainability, despite repeated unqualified audit opinions (WTP). The activity employed a participatory training method, focusing on regulatory understanding about regional financial management, performance-based budgeting, accrual-based financial reporting, and transparency accountability mechanisms. The training involved 25 officials from key agencies (the Finance Agency, the Inspectorate, and technical SKPDs) and was evaluated using pre- and post-tests and group discussions. Results showed a significant increase in participants’ average competency score from baseline to 83.3 in the post-test, with 100% attendance. Outputs included a validated training module, activity documentation, and a draft scientific article for a SINTA-indexed journal. The activity successfully improved understanding of financial management principles, enhanced commitment to transparency and accountability, and laid the foundation for sustainable capacity building. Recommendations include regular follow-up training, institutionalizing internal mentoring, and integrating digital tools for cash and asset management.